Strengthening the Capacity of the Village Deliberation Agency (BPD) of Melikan Village, Wedi District, Klaten Regency, Central Java - Utami Sulistiana; RY. Gembong Rahmadi; Putera Perdana; Juang Gagah Mahardhika (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Many Village Regulations are not preceded by academic studies. As a consequence, the village regulation becomes sociologically incompatible and even contradicts the laws of a higher degree. Departing from this rationale, it is urgent that mentoring activities be carried out for Village Governments in carrying out the preparation of ideal Village Regulations. This method of mentoring activities is carried out by advocating grids both pre-drafting, during preparation, and post-preparation. It is expected that from the assistance activities for the preparation of Village Regulations for Village Governments in Melikan Village, Klaten District, Central Java, there will be outputs in the form of sensitivity of village officials, members of the Village Consultative Board, Community Leaders to increase the knowledge of village officials, members of the Village Consultative Body and Community Leaders to encourage synergistic performance between village officials, members of the Village Consultative Body and Community Leaders in producing village regulations.